Evaluation of risk factors of postpartum urinary retention after vaginal delivery - Djusad, Suskhan (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundUrinary retention is a condition where a person is unable to urinate even after making sufficient efforts. It can be classified as either acute or chronic, as well as overt or covert. Urinary retention can be caused by various factors such as poor detrusor muscle contraction, a decrease in bladder contractility, anatomical anomalies, impaired neurological coordination while urinating, and disruption of outlet relaxation. The objective of this study was to identify the risk factors of postpartum urinary retention (PPUR) after vaginal delivery. MethodsA cross-sectional study was conducted involving 500 female subjects who were in labor. All data obtained including variables such as age, parity, perineal rupture, episiotomy, history of using assisted vaginal birth during labor, and newborn weight, were compared between female subjects with and without postpartum urinary retention. The data were was analyzed using chi square test and multiple logistic regression analyses as a means to identify risk factors for PPUR. Results Among the 500 patients recruited to our study, 68 (13.6%) had PPUR. Episiotomy and parity were found to be potential risk factors for PPUR (OR=1.84;95% CI = 1.06-3.18 and OR=2.19;95% CI = 1.16-4.12, respectively). Severe perineal rupture was not a risk factor of PPUR (OR= 0.82;95% CI =0.82-5.89). ConclusionThe prevalence of PPUR was quite high. Risk factors identified for PPUR were parity and episiotomy. In clinical practice, healthcare providers should pay more attention to women with these risk factors to prevent PPUR.